Effects of combined aerobic and resistance training on gut microbiota and cardiovascular risk factors in physically active elderly women: A randomized controlled trial - Zhong, Fei; Xu, Yongjin; Lai, Hsin-Yi; Yang, Min; Cheng, Lei; Liu, Xinger; Sun, Xiaomin; Yang, Yi; Wang, Jian; Lv, Wen; Huang, Cong (Frontiers in Physiology, 2022)
Background: Exercise can modulate gut microbiota and lower the risk of cardiovascular disease (CVD). However, the association between exercise-induced changes in gut microbiota and CVD risk have not been investigated. Objective: This study determined the effects of exercise training on CVD risk and gut microbiota in physically active elderly women and whether exercise-induced gut microbiota changes were associated with CVD risk. Methods: An 8-week randomized controlled trial was conducted with 14 elderly women assigned to exercise group (n = 8) or control group (n = 6). Physical function, sarcopenic obesity, and metabolic syndrome were evaluated as components of CVD risk. Gut microbiota composition was determined using 16S rRNA gene sequencing. Repeated-measures analysis of variance was used to examine intra-group and inter-group differences. Results: A significant group × time interaction was observed for chair sit-and-reach (F = 8.262, p = 0.014), single-leg standing with eyes closed (F = 7.340, p = 0.019), waist circumference (F = 6.254, p = 0.028), and body fat mass (F = 12.263, p = 0.004), for which the exercise group showed improved trends. The exercise group exhibited significant improvements in skeletal muscle mass (p = 0.041) and fasting blood glucose (p = 0.017). Regarding gut microbiota, a significant interaction was observed for the class Betaproteobacteria (F = 6.822, p = 0.023) and genus Holdemania (F = 4.852, p = 0.048). Conclusion: The 8-week exercise training improved physical function, lowered CVD risk, and modulated relative abundance of gut microbiota associated with CVD in physically active elderly women.